The Effect of Using Web-Based Interactive Learning Media for Vocational High School Students to Understanding of Looping: Qualitative Approach - Dwi Fitria Al Husaeni; Enrico Nabil Qois Budisantoso; Mushfani Ainul Urwah; Nissa Nur Azizah; Putri Zukhruf Dinata; Shandini Apriliany; Herbert Siregar (Journal of Science Learning, 2022)
This study aims to evaluate the effect of the use and development of interactive and visual learning media in learning looping by utilizing a web-based digital platform called Loopers. The research design used a qualitative descriptive with case study approach in-depth interview technique. The subjects of this research are five students of the State Vocational School Pekerjaan Umum, Bandung, Indonesia. We use three phases in conducting research through 1) problem and needs analysis, 2) web design, and 3) implementation and testing. Loopers was developed using the waterfall method. Loopers can demonstrate the implementation of a productive learning process and measure the effectiveness of interactive and visualized learning media. The findings show that Loopers can effectively facilitate experimental demonstrations and written modules. Respondents think this learning media is effective and can increase their interest, motivation, and interest in learning looping material. The next research is to enrich the Loopers feature and conduct trials with larger respondents.